Impact of Structure of Ownership on the Company’s Performance regarding Dividend: Evidence from Pakistan - Shah, Ansar Abbas; Ahmed, Waqar; Anwar, Rizwan; Mohsin, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2022)
It is critical for firms to consider the impact on their structure of ownership and dividends on the execution of the organization when making choices with a view toward maximizing earnings. The focus of this study is on the dividend's and ownership structure's effects on a company's bottom line. The study used a panel-regression analysis to determine impact of foreign ownership, family ownership &institutional ownership, on the financial execution of Pakistani firms. Secondary sources were used for this study's data collection. Using information from the PSEL and the Reports of 74 firms over a 6-year period, we have identified a population of interest consisting of non-financial enterprises included in the KSE-100 index. Foreign ownership dividend payment was all shown to significantly affect business performance in the research. Based on the findings, it seems information is crucial for describing the pattern of dividend distribution and its effect on a betterment of firm. This study is novel in that it examines the relation among ownership structure and dividend performance. Evaluation of the structure of ownership to analyze its influence on business execution to generate returns of high investment, this study will aid firms in making of decision to earn greater revenue and help individuals in making their choice.